The effect of teaching idioms through visual media on idiom comprehension among high school students - Nurqulova, Oydinabonu Sirojiddin qizi; Gaybullayeva, Dildora Fayzullla qizi (The Lingua Spectrum, 2026)
One way to help teens grasp idioms better is by showing them pictures and moving images alongside words. Videos, drawings, or animated clips give real-life settings where phrases make sense. Seeing an expression acted out helps memory stick, especially when paired with spoken or written form. Teachers need fresh ideas, such as drawing scenes or acting out metaphors, to bring lessons alive. Training also plays an important role; educators must learn how to pick strong visuals wisely. When done right, learners pay closer attention and recall meanings longer. Communication skills grow because students start using phrases naturally, not just repeating them again and again. Meaning sticks best when eyes and ears work together. Learning feels less like memorizing and more like discovering. Picture clues stick in your mind, so phrases stay out and come out when speaking feels natural. Because of this, students join in more, question choices, and work together – the class becomes something that moves and breathes.